Ideological Foundations and Cultural Manifestations of Youth Volunteering in Armenia - Vermishyan, Harutyun; Darbinyan, Tatyana (Journal of Sociology: Bulletin of Yerevan University, 2021)
The purpose of this study is to identify the ideological and cultural aspects of youth volunteering ․ The concept of social action by M. Weber and the functional model of volunteering were compared ․ Based on the developed conceptual approach, at the first stage of the study, using online surveys, the most common types of young volunteers in Armenia (goal-rational, value-rational and hybrid) were identified. High-quality interviews were conducted with representatives of each type using the methodology of narrative semiotics, revealing the life experience of Armenian volunteers. Narratives were analyzed using the method of narrative semiotic analysis. The article examines the peculiarities of the formation of civil society and the formation of civic consciousness of Armenian youth, it is shown that the ideological foundations and cultural manifestations of their volunteer activities are rational in nature.
Keywords: Ideology; Culture; Youth; Volunteering; Value-rational Action; Rationally-purposeful Action; Narrative Semiotics